Tongue mucocele and microlith associated with a phlebolith mimicking a hemangioma: A unique case report with its surgical management - Firdoose C.S., Nyer (Journal of Oral Diagnosis, 2019)
Unique variants of oral mucocele such as the mucocele appearing on tongue are consid- ered to be extremely rare. It is important to recognize these unique variants promptly to avoid misdiagnosis. The cases of phleboliths not associated with vascular lesions are also rarely reported in the literature, especially as solitary nodules. Conclusion: The fol- lowing manuscript thereby attempts to present a unique case of a geriatric patient with a combination of Tongue mucocele with microlith mimicking a hemangioma associated with phlebolith along with its diagnosis, clinical presentation and surgical management.